New Direct Oral Anticoagulants (DOAC) and Their Use Today - Heike Schwarb; Dimitrios A. Tsakiris (MDPI AG, 2016)
The ideal anticoagulant is oral, has a wide therapeutic range, predictable pharmacokinetics and pharmacodynamics, a rapid onset of action, an available antidote, minimal side effects and minimal interactions with other drugs or food. With the development of the novel direct oral anticoagulants (DOAC), we now have an alternative to the traditional vitamin K antagonists (VKA) for the prevention and treatment of thrombosis. DOACs have limited monitoring requirements and very predictable pharmacokinetic profiles. They were shown to be non-inferior or superior to VKA in the prophylaxis or treatment of thromboembolic events. Particularly in terms of safety they were associated with less major bleeding, including intracranial bleeding, thus providing a superior benefit for the prevention of stroke in patients with atrial fibrillation. Despite these advantages, there are remaining limitations with DOACs: their dependence on renal and hepatic function for clearance and the lack of an approved reversal agent, whereas such antidotes are successively being made available. DOACs do not need regular monitoring to assess the treatment effect but, on the other hand, they interact with other drugs and interfere with functional coagulation assays. From a practical point of view, the properties of oral administration, simple dosing without monitoring, a short half-life allowing for the possibility of uncomplicated switching or bridging, and proven safety overwhelm the disadvantages, making them an attractive option for short- or long-term anticoagulation.